2022
DOI: 10.3390/diseases10030035
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Gastric Cancer

Abstract: Gastric cancer remains a major killer globally, although its incidence has declined over the past century. It is the fifth most common cancer and the third most common reason for cancer-related deaths worldwide. Gastric cancer is the outcome of a complex interaction between environmental, host genetic, and microbial factors. There is significant evidence supporting the association between chronic inflammation and the onset of cancer. This association is particularly robust for gastrointestinal cancers in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 202 publications
0
27
0
Order By: Relevance
“…Chronic inflammation driven by immune cells is a rather complex process requiring multiple cellular players (e.g., macrophages, lymphocytes) and pivotal regulators, including signaling pathways (e.g., NF-kB, JAK-STAT, TLR, MAPK), growth factors (e.g., VEGF, TGF-ß), as well as inflammatory factors (e.g., cytokines, chemokines), inflammasome, and inflammatory metabolites (e.g., prostaglandins, leukotrienes) , as reviewed by Zhao et al (100). Tumor growth is promoted by an inflammatory response, which in turn is induced by inflammatory mediators that can attract immune cells to the lesion (101). That promotes the perfect conditions for the growth, invasion and metastization of tumor cells, known as the tumor microenvironment (101).…”
Section: Microbiota Interplay In Gastric Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic inflammation driven by immune cells is a rather complex process requiring multiple cellular players (e.g., macrophages, lymphocytes) and pivotal regulators, including signaling pathways (e.g., NF-kB, JAK-STAT, TLR, MAPK), growth factors (e.g., VEGF, TGF-ß), as well as inflammatory factors (e.g., cytokines, chemokines), inflammasome, and inflammatory metabolites (e.g., prostaglandins, leukotrienes) , as reviewed by Zhao et al (100). Tumor growth is promoted by an inflammatory response, which in turn is induced by inflammatory mediators that can attract immune cells to the lesion (101). That promotes the perfect conditions for the growth, invasion and metastization of tumor cells, known as the tumor microenvironment (101).…”
Section: Microbiota Interplay In Gastric Carcinogenesismentioning
confidence: 99%
“…Tumor growth is promoted by an inflammatory response, which in turn is induced by inflammatory mediators that can attract immune cells to the lesion (101). That promotes the perfect conditions for the growth, invasion and metastization of tumor cells, known as the tumor microenvironment (101).…”
Section: Microbiota Interplay In Gastric Carcinogenesismentioning
confidence: 99%
“…In recent decades, several studies have demonstrated that inflammation can involve every process of tumor development, progression, metastasis, and treatment resistance, suggesting that inflammation is one of the hallmarks of cancer [ 1 , 2 , 3 ]. Due to of the notable association of gastric carcinogenesis with Helicobacter pylori infection and Epstein–Barr virus infection, gastric cancer has been considered to be closely associated with infection and chronic inflammation [ 4 ]. In clinical studies of gastric cancer patients, serum inflammatory markers such as C-reactive protein, the neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR), which can reflect the degree of host inflammatory response, were found to be significant predictors of cancer progression and survival [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (Machlowska et al , 2020) have reported that multiple risk factors can affect the occurrence and development of GC, including Helicobacter pylori (H. pylori ) infection, obesity, current alcohol consumption, current smoking, and excessive sodium intake. In addition, inflammation is also an important factor in the development of GC, and genetic factors involved in inflammation may play an important role in the development of GC (Ji et al , 2021; Jaroenlapnopparat et al , 2022).…”
Section: Introductionmentioning
confidence: 99%